Agronomic characteristics and radiosensitivity level of the Rubaru shallot irradiated by gamma rays - Persada, Olfa; Fairuzia, Fazat; Yuliani, Farida; Arini, Nindya (Indonesian Journal of Agricultural Research, 2025)
The Rubaru shallots are resistant to various abiotic and biotic stresses, such as high salinity and Fusarium wilt disease. However, this shallot was unable to flower even after flowering was induced by cold temperatures and increasing day length, as well as polyploidy methods. Therefore, efforts are needed to increase the genetic diversity of the Rubaru variety of shallots through the induction of physical mutations with gamma ray irradiation. This research aims to determine the agronomic characteristics and radiosensitivity level of the Rubaru shallot (Allium cepa L.) resulting from gamma-ray irradiation. The research used a Randomized Complete Block Design (RCBD) with one factor, namely the dose of gamma ray irradiation (G), which consists of 5 levels as follows: G0 (control), G1 (2 Gy), G2 (4 Gy), G3 (6 Gy), G4 (8 Gy). The gamma-ray irradiation treatment had a very significant effect on agronomic characteristics, namely plant length and number of leaves, number of bulbs per cluster, bulb diameter, bulb fresh weight per cluster, bulb dry weight per cluster, and weight of the largest bulb per cluster. Gamma irradiation treatment with a dose of 2 Gy produced the highest number of bulbs and bulb diameter, with the largest weight of < 3g. Meanwhile, a dose of 8 Gy had a real effect on all parameters in inhibiting the growth of the Rubaru shallot. The calculated lethal dose (LD50) value is 6.18 Gy.